The Association of Serum Total Bile Acids With Bone Mineral Density in Chinese Adults Aged 20–59: A Retrospective Cross-Sectional Study - Liu, Jingxin; Chen, Yuxing; Luo, Qi (Frontiers in Endocrinology, 2022)
Objective: According to a recent study, serum total bile acids (TBA) may preserve lumbar bone mineral density (BMD) in Cushing syndrome patients, and BMD is directly linked to bone health. We were interested in examining the association between TBA and in Chinese adults aged 20–59. Methods: We retrospectively analyzed the physical examination results of 2490 general healthy subjects in Hainan West Central Hospital. femoral neck BMD and TBA were measured, and the relationship between TBA and femoral neck BMD was evaluated by curve fitting, a generalized additive model, and multiple linear regression analysis. Results: The fitted smooth curve and generalized additive model showed a nonlinear relationship between TBA and femoral neck BMD, and a positive correlation between TBA and femoral neck BMD was found after we made adjustments for the potential confounders. Conclusion: TBA is positively associated with femoral neck BMD in Chinese adults aged 20-59.